On the reversed LCOE calculation: Design constraints for wave energy commercialization. (June 2017) - de Andres, A.; Medina-Lopez, E.; Crooks, D.; Roberts, O.; Jeffrey, H.
Highlights: The reversed LCOE method is presented as a tool to estimate limits for expenditure. Moreover, a specified characterisation of technical parameters involved is given. Five different types of wave energy devices are analysed. A comparison is made with devices currently under development. A comparison with offshore wind is carried out to highlight cost reduction paths. Abstract: The purpose of this work is to provide an innovative tool based on the classic Levelised Cost of Energy (LCOE) which gives an overview of the limits for the technical parameters of Wave Energy Converters (WECs). In this case, the LCOE calculation procedure is reversed: the LCOE target is set in the first instance, followed by the calculation of the Average Energy Production (AEP) based on different scenarios. Then, the Capital and Operating Expenditures (CAPEX and OPEX) are calculated and percentages per cost centre are assigned in order to find the cost of each technical parameter, e.g. the structure, Power Take-Off (PTO), connections, mooring and installation costs. With this reversed LCOE the upper costs limits for a WEC were obtained. Moreover, an approximation of parameters such as the maximum mass of steel, mooring length or number of interventions per year are given. Five WECs classes are analysed in this paper: Oscillating Water Column (OWC), overtopping devices, heaving devices, fixed Oscillating Wave Surge Converter (OWSC) and floating OWSC. An extensive comparison with actual devices is made. Finally, a comparison with the limits in the Offshore Wind Energy sector is given as a check of the cost-reduction potential of Wave Energy. As a conclusion, although in a primary stage of development, commercial WEC projects have the potential to be competitive with the Offshore Wind Energy industry.